Narrative change in psychotherapy: differences between good and bad outcome cases in cognitive, narrative, and prescriptive therapies - Moreira, Paulo (2008)
This study aimed to clarify the relationship between changes in the patients’ narratives and therapeutic outcomes. Two patients were selected from three psychotherapeutic models (cognitive, narrative, and prescriptive therapies), one with good therapeutic outcome and the other with bad therapeutic outcome. Sessions from the initial, middle, and final phases for each patient were evaluated in terms of narrative structural coherence, process complexity, and content diversity. Differences between patients’ total narrative production were found at the end of the therapeutic process. Good outcome cases presented a higher statistically significant total narrative change than poor outcome cases